Poznavanje lestvice mednarodne iniciative za standardizacijo diet pri strokovnih sodelavcih tima za (re)habilitacijo otrok - Slana, Nuša (Rehabilitacija (Ljubljana), 2021)
Introduction: Feeding and swallowing disorders (FSD) are common in children with neurological disorders. One of the main measures in treating FSD in adults as well as children is the modification of food texture and liquid consistency. The International Dysphagia Diet Standardization Initiative (IDDSI) has prepared guidelines for classifying food and liquid based on texture and thickness. Our goal was to assess the knowledge of employees from the Department of (Re)habilitation of Children about adequate modification of food and liquid. We also wanted to assess their knowledge of IDDSI guidelines and mainly the reliability of determining different IDDSI levels before and after a workshop, which was prepared to improve the knowledge of IDDSI levels and to improve the reliability in determining different levels. Methods: We included 24 employees of different professional profiles who attended the workshop about the modification of food and liquid based on the IDDSI guidelines. For the purpose of the study, a questionnaire for assessing the knowledge about adequate modification of food and liquid and a questionnaire for assessing food and liquid based on IDDSI guidelines were prepared, which the participants completed before and after the workshop. Results: The results revealed that before attending the workshop the employees felt less informed about the adequate food and liquid for persons with FSD and less competent for offering safe food and drinks. After the workshop the self-assessment of knowledge and competence significantly improved. The number of correctly determined IDDSI levels was significantly higher as well. Conclusion: Our study revealed the problem of a lack of knowledge of adequately modified food and liquid. It is necessary that all employees from the Department of (Re)habilitation of Children are informed of the basic IDDSI guidelines. The workshop proved to be an effective way of informing the employees about the treatment of persons with FSD. The study also revealed the problem of non-standardised terminology for describing food and liquid. Internationally standardised and unambiguous terminology is necessary for more effective communication among healthcare workers as well as for safer treatment of FSD.
Keywords: Child; feeding and swallowing disorders; food texture; FSD; gostota tekočine; IDDSI; International Dysphagia Diet Standardization Initiative; liquid consistency; Mednarodna iniciativa za standardizacijo diet; motnje hranjenja in požiranja; otrok; Rehabilitation; tekstura hrane